2016
DOI: 10.1128/aem.01336-16
|View full text |Cite
|
Sign up to set email alerts
|

Role of Phosphate Transport System Component PstB1 in Phosphate Internalization by Nostoc punctiforme

Abstract: In bacteria, limited phosphate availability promotes the synthesis of active uptake systems, such as the Pst phosphate transport system. To understand the mechanisms that facilitate phosphate accumulation in the cyanobacterium Nostoc punctiforme, phosphate transport systems were identified, revealing a redundancy of Pst phosphate uptake systems that exists across three distinct operons. Four separate PstB system components were identified. pstB1 was determined to be a suitable target for creating phenotypic mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Here, we showed that strain P5 also carries the pst operon, including pstS , pstC , pstA and pstB . PstS is a binding protein, PstC and PstA are two integral inner membrane proteins, and PstB is an ATP-binding protein 39 . Therefore, strain P5 takes up inorganic phosphate partially through a phosphate transport system.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we showed that strain P5 also carries the pst operon, including pstS , pstC , pstA and pstB . PstS is a binding protein, PstC and PstA are two integral inner membrane proteins, and PstB is an ATP-binding protein 39 . Therefore, strain P5 takes up inorganic phosphate partially through a phosphate transport system.…”
Section: Discussionmentioning
confidence: 99%
“…Duplicate pst clusters in cyanobacteria lacking pitA have been shown to favor distinct P i ranges to cater for starvation and replete conditions [ 105 ]. As Microcoleus has higher velocity pitA , the duplicate pst operons of Microcoleus instead might vary in their capacity for P i accumulation under limiting conditions [ 106 ]. The high-affinity phosphate uptake system also appears to play a critical role in biofilm formation [ 107 ].…”
Section: Resultsmentioning
confidence: 99%
“…As noted above, the specific response to P starvation was constituted by the upregulation of the P acquisition systems, including those in control of the P i uptake that are well-studied both in model heterotroph bacteria [ 50 ] and cyanobacteria [ 23 , 49 ]. The cyanobacterial cells, including those of the strain studied in this work, take up P i through the pstABCS transporter family, including ATP-driven ABC-type P i pumps ( Table 1 , [ 22 ]) crucial for P accumulation [ 63 ]. It is regulated by the two-component system operating via the phosphorylation/dephosphorylation of phoB and phoR or their orthologs sphS and sphR [ 49 ], with participation of the repressor phoU (or sphU ).…”
Section: Discussionmentioning
confidence: 99%